Adobe mixtures reinforced with fibrillated polypropylene fibers: Physical/mechanical/fracture/durability performance and its limits due to fiber clustering. (8th August 2022) - Burbano-Garcia, C.; Araya-Letelier, G.; Astroza, R.; Silva, Y.F.
Graphical abstract: Highlights: Fibrillated polypropylene fibers (FPFs) are used to reinforce adobe mixtures (AMs). Bulk density and compressive and flexural strength decrease as FPF dosage increases. Water erosion resistance and flexural toughness increase as FPF dosage increases. The FPFs morphology and the AMs manual confection promote fiber clusters generation. FPF dosages should be small since clusters greatly reduce the mechanical strength. Abstract: This study assesses the feasibility of the incorporation of fibrillated polypropylene fibers (FPFs), an engineered multidimensional and multifilament fiber mostly used to reinforce concrete mixtures, into adobe mixtures (AMs), a traditional and manually-made material used to produce adobe blocks. The incorporation of FPFs was assessed using increasing dosages (0%, 0.25%, 0.5%, and 1% in wt% of clay soil) of FPFs. These fibers were gradually added and mixed with the clayey soil prior to incorporation of water to promote uniform mixtures with adequate fiber distribution to reduce the formation of fiber clusters. The impact of FPFs was evaluated in terms of its effects on the bulk density (physical), compressive and flexural strength (mechanical), flexural toughness indices (fracture) and water erosion resistance (durability) of AMs. Results indicate that increasing dosages of FPFs monotonically reduce average values of bulk density, as well as compressive and flexural strength of AMs. On the other hand, these increasing dosages of FPFs monotonically increase average values of water erosion resistance as well as flexural toughness indices, varying the flexural failure mode from brittle (unreinforced AM) to ductile (reinforced AMs) because of the adequate bonding and FPF-bridging effect after the crack generation as confirmed by instrumentation as well as digital image correlation evaluations implemented in this study. The significant reductions of bulk densities and compressive and flexural strengths obtained for fiber-reinforced AMs were related to the increasing number of fiber clusters found for increasing dosages of FPFs within the fiber-reinforced mixtures, which was evaluated using scanning electron microscopy analyses. For example, positively the AM incorporating 1% of FPFs increased, on average, the flexural toughness by 674% and reduced the bulk density and water erosion depth by, on average, 9% and 64%, respectively, when compared to the unreinforced AM. However, this large dosage of FPFs also generated a significant reduction of the compressive strength (60% on average) and the flexural strength (43% on average) when compared to the plain mixture. On the other hand, a small dosage of FPFs (0.25%) generated less significant improvements in terms of flexural toughness, bulk density, and water erosion (on average, increment of 58% and reductions of 2% and of 38%, respectively, when compared to the unreinforced AM). Yet, the latter mixture presented reductions, on average, of compressive and flexural strengths of 24% and 16%, respectively, when compared to the plain mixture, and these reductions were significantly smaller than the reductions obtained by the largest FPF dosage, due to the significantly smaller number of fiber clusters presented by the 0.25% dosage when compared to the 1% dosage. Finally, the mechanical performance limitations exhibited by the incorporation of FPFs, especially in large dosages, are related to generated fiber clusters due to the inherent morphology of these FPFs as well as the traditional manual confection process of AMs. Therefore, this study recommends the implementation of FPFs in AMs, but in small dosages and/or suggests the implementation of a mechanical mixing/compaction process that guarantee a more uniform fiber distribution that reduces the generation of fiber clusters.